2014
DOI: 10.1155/2014/230346
|View full text |Cite
|
Sign up to set email alerts
|

Osteodifferentiated Mesenchymal Stem Cells from Bone Marrow and Adipose Tissue Express HLA-G and Display Immunomodulatory Properties in HLA-Mismatched Settings: Implications in Bone Repair Therapy

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells that can be obtained from several sources such as bone marrow and adipose tissue. Depending on the culture conditions, they can differentiate into osteoblasts, chondroblasts, adipocytes, or neurons. In this regard, they constitute promising candidates for cell-based therapy aimed at repairing damaged tissues. In addition, MSCs display immunomodulatory properties through the expression of soluble factors including HLA-G. We here analyse both immunogenicity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 23 publications
2
49
0
Order By: Relevance
“…In fact, the suppressive effect was enhanced by ELCs in comparison with WJ‐MSCs and largely exerted under conditions of contact. Similar results were obtained after differentiation of MSCs into adipose, bone and cartilage lineages 14 , 15 , 47 . These results led us to investigate the effects of differentiated cells on: (1) a population of cells enriched in CD3 + T cells, the major effector cells of adaptive immunity; 48 and (2) NK cells, as they represent the major effector of the innate immune response exhibiting a critical role in early host defense against infections and cancer 49 …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In fact, the suppressive effect was enhanced by ELCs in comparison with WJ‐MSCs and largely exerted under conditions of contact. Similar results were obtained after differentiation of MSCs into adipose, bone and cartilage lineages 14 , 15 , 47 . These results led us to investigate the effects of differentiated cells on: (1) a population of cells enriched in CD3 + T cells, the major effector cells of adaptive immunity; 48 and (2) NK cells, as they represent the major effector of the innate immune response exhibiting a critical role in early host defense against infections and cancer 49 …”
Section: Discussionsupporting
confidence: 64%
“…Similar results were obtained after differentiation of MSCs into adipose, bone and cartilage lineages. 14,15,47 These results led us to investigate the effects of differentiated cells on: (1) a population of cells enriched in CD3 + T cells, the major effector cells of adaptive immunity; 48 and (2) NK cells, as they represent the major effector of the innate immune response exhibiting a critical role in early host defense against infections and cancer. 49 We noticed that ELCs, and to a lesser extent WJ-MSCs, suppressed the proliferation of activated CD3 + T cells, mainly under cell-cell contact conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1517 Interestingly, fracture leads to suppression of the immune system, 18 with a local increase in the number of induced T regulatory (iT REG ) cells that suppress active adaptive immune responses within the fracture callus. 19 Studies have further shown that mesenchymal stem cells actively maintain a hypoimmunogenic state 20,21 through the production of immunosuppressive paracrine factors, 2224 or through the direct actions of these cells on immune-cell populations, including T cells. 25,26 Such effects suggest that these cells impart immune tolerance throughout the early stages of endochondral bone formation and provide protection to the developing tissues by suppressing allo-proliferation of T cells during stem-cell recruitment and cartilage formation.…”
Section: Introductionmentioning
confidence: 99%
“…]. For example, human bone marrow (BM)‐derived MSC have been reported to maintain their ability to suppress the proliferation of T cells from healthy individuals or rheumatoid arthritis (RA) patients following differentiation into osteoblasts or chrondocytes . Moreover, BMMSC‐derived chrondocytes reduced T‐cell activation and their ability to release proinflammatory mediators in vitro .…”
Section: Introductionmentioning
confidence: 99%